Are men getting more emotional? Critical sociological perspectives on men, masculinities and emotions - de Boise, Sam; Hearn, Jeff (The Sociological Review, 2017)
Sociological research, influenced by feminist and other critical perspectives, has noted how men’s emotional inexpressiveness was influenced, and supported, by patriarchal privilege. Such approaches have argued that ‘inexpression’ needs to be broken down in order to build gender equality and improve men’s own wellbeing. Emerging research has, however, challenged the argument that men are ‘emotionally inexpressive’ on two main premises: that, as a result of feminist critiques, many men now practise ‘softer’ or ‘more emotional’ forms of masculinity; second, that emotions always influence social action and so need to be better incorporated into sociological accounts of men’s behaviour. Yet these approaches entail some conceptual confusion as to what emotions are, how they link to social action and whether men’s emotions are inherently transformative for gender relations. This article first details how emotions and masculinity have been theorized in feminist-inspired approaches. It outlines recent work on emotions, men and masculinities before arguing for an understanding of emotions that engages with both physiologically grounded and postconstructionist debates. It finally suggests incorporating a material-discursive approach to men’s emotions, through feminist work on affect, which is attentive to the political dimensions of ‘increasing emotionality’ in order to contribute to a developing field of sociological research.
https://www.researchgate.net/publication/313022582_Are_men_getting_more_emotional_Critical_sociological_perspectives_on_men_masculinities_and_emotions
Keywords: approches et analyses; discipline; genre; inégalités; masculinité; privilèges; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppression; émotions

Men's intrusion, women's embodiment: a critical analysis of street harassment - Vera-Gray, Fiona (Routledge, 2017)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité; angleterre; approches et analyses; corps; discipline; europe; harcèlement de rue; patriarcat; phénoménologie; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; systèmes d'oppression; thématiques; violences